THE INFLUENCE OF FLIGHT SAFETY FACILITIES AGAINST SECURITY IN THE CARGO TERMINAL MINANGKABAU INTERNATIONAL AIRPORT - Andi Gunawan Harahap, Novri; Rinaldi, Ridho; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Minangkabau International Airport is an airport located in Padang Pariaman, West Sumatra (ICAO Code : WIEE ; IATA Code : PDG), has a Domestic Terminal, VIP Terminal, International Terminal, and Cargo Terminal. At the cargo terminal, problems were found that arose due to a lack of security facilities and personnel. So we need a study that can provide an explanation regarding aviation security facilities at the Minangkabau International Airport Cargo Terminal. The purpose of this study was to determine the effect of aviation security facilities on security at the cargo terminal capable of providing security for goods and cargo. The type of this research is descriptive quantitative using data obtained from observations, distributing questionnaires, and literature studies. Respondents from the questionnaire were Aviation Security and Angkasa Pura Cargo personnel, with a total sample of 61 people. The results of the discussion, there is an influence of variable X (aviation security facilities) on Y (security at the cargo terminal) has a relationship or correlation between variables with 0.78 (high, strong correlation) and the R square value is 0.608 or 60.8 % . There are things that need to be optimized in terms of the influence of aviation security facilities on security at the Minangkabau International Airport Cargo Terminal, the need to increase the number of Aviation Security personnel licensed by Junior Avsec to operate 1 x-ray machine with a minimum of 3 people and the need for security facilities is not yet adequate, such as the absence of a Walk Through Metal Detector.